The Influence of Maritime Regulations and Company Policies on the Human Factor Accident Rate as an Intervening Variable (Case Study at PT. Marina Logistik Sejahtera) - Setiadi, Aries; Malau, April Gunawan; Gusti, Ayudhia Pangestu (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the influence of maritime regulations and company policies on accident rates with human factors as an intervening variable at PT. Marina Logistics Sejahtera. The main issue examined is the extent to which maritime regulations and internal company policies can reduce shipping accident rates, as well as how human factors act as a mediator in strengthening the relationship among these variables. The population of this research consists of all crew members working at PT. Marina Logistik Sejahtera, with a total sample of 89 respondents. The sampling technique employed was purposive sampling using the Slovin formula. This study applied a quantitative method with a cross-sectional approach, in which data were collected through a Likert-scale questionnaire. The collected data were analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM) through several stages, including validity testing, reliability testing, and path analysis. The results indicate that maritime regulations and company policies have a positive and significant effect on both human factors and accident rates. Furthermore, human factors are proven to be an intervening variable that strengthens the influence of maritime regulations and company policies in reducing accident rates. Moreover, company policies have a more dominant effect compared to maritime regulations in shaping human factors and decreasing accident rates. The conclusion of this study is that improving regulatory compliance and strengthening internal policies based on training and crew competence are crucial strategies to reduce accident risks. Based on these findings, it is recommended that the company enhance its safety training system, improve regulatory monitoring mechanisms, and develop a risk management program focused on improving the quality of maritime human resources